Prospective, randomized, multicenter study of intraosseous basivertebral nerve ablation for the treatment of chronic low back pain: 12-month results. Issue 8 (24th May 2021) - Smuck, Matthew; Khalil, Jad; Barrette, Kevin; Hirsch, Joshua Adam; Kreiner, Scott; Koreckij, Theodore; Garfin, Steven; Mekhail, Nagy
Abstract : Introduction: Vertebral endplates, innervated by the basivertebral nerve (BVN), are a source of chronic low back pain correlated with Modic changes. A randomized trial comparing BVN ablation to standard care (SC) recently reported results of an interim analysis. Here, we report the results of the full randomized trial, including the 3-month and 6-month between-arm comparisons, 12-month treatment arm results, and 6-month outcomes of BVN ablation in the former SC arm. Methods: Prospective, open label, 1:1 randomized controlled trial of BVN ablation versus SC in 23 US sites with follow-up at 6 weeks, 3, 6, 9, and 12 months. SC patients were re-baselined and followed up for 6 months post BVN ablation. The primary endpoint was the between-arm comparison of mean Oswestry Disability Index (ODI) change from baseline. Secondary endpoints were Visual Analog Scale (VAS), Short Form (SF-36), EuroQual Group 5 Dimension 5-Level Quality of Life (EQ-5D-5L), responder rates, and rates of continued opioid use. Results: 140 were randomized. Results from BVN ablation (n=66) were superior to SC (n=74) at 3 months for the primary endpoint (mean ODI reduction, difference between arms of −20.3 (CI −25.9 to −14.7 points; p<0.001)), VAS pain improvement (difference of −2.5 cm between arms (CI −3.37 to −1.64, p<0.001)) and quality of life outcomes. At 12 months, basivertebral ablation demonstrated a 25.7±18.5 point reduction in mean ODI (p<0.001), and a 3.8±2.7 cm VAS reduction (p<0.001) from baseline, with 64% demonstrating ≥50% reduction and 29% pain free. Similarly, the former SC patients who elected BVN ablation (92%) demonstrated a 25.9±15.5 point mean ODI reduction (p<0.001) from baseline. The proportion of opioid use did not change in either group (p=0.56). Discussion/Conclusion: BVN ablation demonstrates significant improvements in pain and function over SC, with treatment results sustained through 12 months in patients with chronic low back pain of vertebrogenic origin.